ACTIVITY OF RED FRUIT (PANDANUS CONOIDEUS LAM.) OIL IN STREPTOZOTOSIN-INDUCED PERIPHERAL DIABETIC NEUROPATHY RAT MODEL WITH ANXIETY AND DEPRESSIVE BEHAVIOR - Tri Lestari, Indah
Diabetic Peripheral Neuropathy (NPD) is the most common complication of diabetes in diabetics, manifested in abnormal sensory symptoms such as hyperalgesia (increased pain sensitivity) and allodynia (painful sensation to harmless stimuli). Persistent pain in NPD patients is known to have a negative impact on psychosocial function by increasing levels of anxiety and depression which collectively reduce the quality of life of diabetic patients. Red fruit oil (RFO) is a natural product widely used in the food and medical fields with benefits such as antidiabetic, anti-inflammatory, and antioxidant. This study aims to investigate the potential effects of RFO on diabetic peripheral neuropathy with depressive and anxiety behavior in a rat model induced by Streptozotosin (STZ). In this study, the diabetes model was performed by intraperitoneal injection of STZ 55mg/kg BW with citrate buffer pH 4.5. The success of induction was validated by increased blood glucose levels, increased food intake, drinking, increased urine volume and histopathological changes in the pancreas and liver. In this study, the STZ-induced diabetes group experienced increased blood glucose levels, increased food intake, increased drinking, and increased urine volume until week 6. RFO administration for 3 weeks was able to reverse diabetes. RFO was also found to repair pancreatic beta cell damage and hepatic vascular diameter of the rats. NPD testing was performed using thermal hyperalgesia and cold allodynia methods. In the cold allodynia test after 3 weeks of treatment, it was observed that the latency time to cold stimuli in the NPD group (4.15 ± 0.33 seconds), which was given a vehicle after induction, and the RFO 0.3 mL/kg group (4.39 ± 0.42 seconds) showed a significant decrease in latency time (P <0.05) compared to the normal group (15.09 ± 0.45 seconds). Meanwhile, the pregabalin 30mg/kg group (9.39 ± 0.58 seconds), RFO 0.6 mL/kg (6.46 ± 0.41 seconds) and RFO 1.2 mL/kg (7.14 ± 0.46 seconds) showed a significant increase in latency time (P <0.05) when compared to the NPD group. A similar pattern was observed in the results of thermal hyperalgesia testing, after 3 weeks of treatment it was observed that the latency time to heat stimulation in the NPD group (3.94±0.75 seconds) and the RFO 0.3 mL/kg group (4.34±0.30 seconds) showed a significant difference (P<0.05) when compared to the normal group (10.94±0.09 seconds). Meanwhile, the pregabalin group (9.38±0.46 seconds), RFO 0.6 mL/kg (6.54±1.06 seconds) and RFO 0.6 mL/kg (6.82±0.48 seconds) showed a significant increase in latency time (P<0.05) when compared to the NPD group. Anxiety behavior testing was conducted using the elevated plus maze (EPM) and open field (OF) methods. In the EPM test, a decrease in the occupation time of the center of the apparatus and exploration distance was observed in the NPD group (3.25 ± 2.63 seconds; 0.35 ± 0.22 m) when compared to the normal group (17.75 ± 8.732 seconds; 1.059 ± 0.206 m), which represents a sign of anxiety through open spaces. Administration of RFO 0.6 mL / kg (14.50 ± 2.64 seconds; 0.97 ± 0.31 m) and RFO 1.2 mL / kg (16.25 ± 4.71 seconds; 1.163 ± 0.22 m) and pregabalin (13.75 ± 3.94 seconds; 1.00 ± 0.25 m) increased exploration distance and time in open space The results OF test showed a decrease in distance traveled and time spent in the center area of the apparatus that was significantly different (P<0.05) in the NPD group (0.41±0.38 seconds; 0.47±0.06 m) when compared to the normal group (2.50±0.57 seconds; 2.83±0.11 m). Administration of RFO 0.6 mL/kg (3.25±1.50 seconds; 2.046±0.74 m), and RFO 1.2 mL/kg (3.50±1.73 seconds; 2.28±0.30 m) and pregabalin 30mg/kg (2.50±1.73 seconds; 0.89±0.11 m) showed an increase in time in the middle of the space and exploration distance that was significantly different (P<0.05) in the OF test. Depression testing was carried out using the forced swimming test (FST) method by calculating immobility time. NPD rats (139.30±16.30 seconds) showed a significantly different increase in immobility time (P<0.05) when compared to the normal group (22.00±2.94 seconds). Administration of RFO 0.6 mL/kg (19.00±6.37 seconds) and RFO 1.2 mL/kg (20.00±11.05 seconds) and pregabalin 30 mg/kg (32.00±18.83 seconds) significantly (P<0.05) decreased immobility time. The results of the behavioral test were confirmed by testing oxidative, inflammatory, plasticity, and histopathological parameters on the sciatic nerve and spinal cord. The oxidation parameters tested included malondialdehyde (MDA), glutathione (GSH), catalase, and NRF2 levels. While the inflammatory parameters included IL-6, TNF-a, NFkB and iNOS levels. The plasticity parameters were measured by measuring BDNF and synaptophysin levels. The results of measuring MDA levels, in the sciatic nerve and spinal cord respectively, showed that there was a significant increase (P<0.05) in the NPD group (177.30±11.76 mM; 205.20±11.65 mM), when compared to the normal group (94.42±12.99 mM; 129.40±4.33 mM). Administration of RFO 0.6 mL/kg (117.50±17.57 mM; 144.80±12.39 mM) and 1.2 mL/kg (128.00±13.90 mM; 121.90±4.21 mM) significantly decreased MDA levels (P<0.05). Pregabalin was also observed to decrease MDA levels (172.80±4.54 mM; 144.80±4.70 mM). In the measurement of GSH levels in the sciatic nerve and spinal cord, a significant decrease (P<0.05) was observed in the NPD group (0.18±0.02 mg/dL; 0.36±0.02 mg/dL) compared to the normal group (0.33±0.08 mg/dL; 0.96±0.24 mg/dL). Levels again increased significantly (P<0.05) after administration of RFO 0.6 mL/kg (0.35±0.02 mg/dL; 0.56±0.13 mg/dL), RFO 1.2 mL/kg (0.48±0.05 mg/dL; 0.53±0.03 mg/dL) and pregabalin (0.26±0.02 mg/dL; 0.48±0.04 mg/dL). A decrease in catalase levels in the sciatic nerve and spinal cord was also observed in the NPD group (2.19±0.05 U/mL; 1.79±0.24 U/mL) significantly different (P<0.05) when compared to the normal group (3.31±0.37 U/mL; 2.49±0.13 U/mL). Levels increased again significantly (P<0.05) after administration of RFO 0.6 mL/kg (2.95±0.25 U/mL; 2.37±0.20 U/mL), RFO 1.2 mL/kg (3.10±0.53 U/mL; 2.34±0.28 U/mL) and pregabalin (2.40±0.10 U/mL; 2.07±0.10 U/mL). The levels of NRF2 in the sciatic nerve and spinal cord decreased in the NPD group (765.00±29.96 ng/mL; 710.10±92.51 ng/mL) compared to the normal group (812.20±57.64 ng/mL; 749.60±35.89 ng/mL). The levels increased again after administration of RFO 1.2 mL/kg (880.60±61.36 ng/mL; 826.30±31.96 ng/mL) and pregabalin (819.30±41.32 ng/mL; 846.60±22.31 ng/mL). The levels of proinflammatory cytokine IL-6 in the sciatic nerve and spinal cord of the NPD group (113.0±8.120 pg/mL; 212.2±16.31 pg/mL) showed a significant increase (P<0.05) compared to the normal group (68.98±6.246 pg/mL; 152.8±8.159 pg/mL). Pregabalin administration improved IL-6 parameters (101.9±3.55 pg/mL; 150.20±5.66 pg/mL). RFO administration 0.6 mL/kg (96.32±5.042 pg/mL; 176.5±6.439 pg/mL). significantly (P<0.05) reduced IL-6 levels in the sciatic nerve and spinal cord. Similar results occurred after administration of 1.2 mL/kg RFO (95.66±4.297 pg/mL; 168.2±6.994 pg/mL). Increased proinflammatory cytokine TNF- ?in the sciatic nerve and spinal cord in the NPD group (35.21±4.90 pg/mL; 59.04±16.36 pg/mL) increased significantly (P<0.05) compared to the normal group (21.19±1.10 pg/mL; 23.36±2.45 pg/mL). Administration of pregabalin improved TNF-?parameters (18.30±1.80 pg/mL; 25.55±4.240 pg/mL). RFO 0.6ml/kg (21.25±2.697 pg/mL; 29.36±4.252 pg/mL) and RFO 1.2mL/kg (19.25±0.236 pg/mL; 24.54±3.223 pg/mL) restored TNF-?levels in the sciatic nerve and spinal cord. A similar pattern was also observed in NF?B, which was significantly increased (P<0.05) in the NPD group (5.60±0.62 ng/mL; 4.78±0.59 ng/mL) compared to the normal group (4.61±0.16 ng/mL; 3.28±0.40 ng/mL). Pregabalin administration improved NF?B parameters (3.624±0.3344 ng/mL) only in the spinal cord. Administration of RFO 0.6 mL/kg (4.685±0.5213 ng/mL) and RFO 1.2 mL/kg (4.624±0.2517 ng/mL) restored NF?B levels significantly (P<0.05) only in the sympathetic nerves. The inflammatory factor iNOS was significantly increased (P<0.05) in the NPD group (60.19±2.72 ng/mL; 58.00±3.89 ng/mL) compared to the normal group (51.00±1.74 ng/mL; 47.02±6.38 ng/mL). Pregabalin administration improved iNOS parameters (49.73±3.02 ng/mL; 53.37±2.40 ng/mL) in the sciatic nerve and spinal cord. Administration of RFO 0.6 mL/kg (47.77±1.12 ng/mL) and RFO 1.2 mL/kg (45.90±0.82 ng/mL) restored iNOS levels significantly (P<0.05) only in the spinal cord. The results of histopathological assesment of the sciatic nerve and spinal cord, both from transverse and longitudinal sections, showed significant changes (P<0.05) in the NPD group when compared to the normal group. The changes observed were gliation and demyelization of the sciatic nerve, as well as vascular dilation in the spinal cord. Administration of pregabalin and RFO 0.6 and 1.2 mL/kg significantly improved these histological changes (P<0.05). In general, this study shows that RFO can improve NPD in the STZ-induced rat model along with the anxiety and depressive behavior that follows by targeting the oxidative and inflammatory pathways in the spinal cord and sciatic nerve. These results, further, imply the potential for RFO to be developed as a mode of treatment for NPD.